A renovação conciliar do ministério episcopal em Dom Jorge Marcos de Oliveira - Sobrinho, Felipe Cosme Damião (2024)
Through an analysis of sources, this research presents biographical aspects of Bishop Jorge Marcos de Oliveira, the first diocesan bishop of Santo André, and the process of hermeneutics and reception of the Second Vatican Council. It is presented elements of his formation for the priesthood, marked by the influence of Cardinal Sebastião Leme da Silveira Cintra. Also his work as a member of the clergy of the Archdiocese of São Sebastião do Rio de Janeiro, where he was auxiliary bishop at the time that Cardinal Jaime de Barros Câmara was the diocesan archbishop. It is reported his social work in the context of pre-conciliar period, with the groups of Catholic Action and in the favelas of Rio de Janeiro, that profoundly marked his personal understanding of ordained ministry. As diocesan bishop of Santo André, in the early years of his ministry, the Prelate overcame the ideologies of the anti-communist discourse of the time, both in the ecclesial and socio-political realities. He worked in defense of the labor’s movement, promoting a socio-transformative pastoral activity. With the celebration of the Second Vatican Council, as a Conciliar priest in (all) the four sessions, Bishop Marcos took an special interest in the drafting of the Pastoral Constitution Gaudium et Spes. Precisely because he recognized the Church's openness to dialogue and service to society, fact which would mark the renewal of his episcopal ministry. Given his openness to social problems, he was persecuted before and after the Vatican II Council, being one of the first members of the Brazilian Catholic hierarchy to denounce the arbitrariness of the military dictatorship established in 1964. The text is illuminated by the bishop’s charismatic authority. Who, far from exercising his authority from a perspective of domination, aroused a new kind of protagonism in the Church and in society. Promoting what today, with the pontificate of Pope Francis, we call integral evangelization. Being, above all, a “shepherd with the smell of the sheep"